2007
DOI: 10.1016/j.neulet.2007.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal quantification of tumor necrosis factor-alpha and interleukin-10 after crush injury in rat sciatic nerve utilizing immunohistochemistry

Abstract: The purpose of this study was to investigate quantitatively the longitudinal temporal, spatial changes of the tumor necrosis factor-alpha (TNF) and interleukin-10 (IL-10) immunopositive cells during Wallerian degeneration and the following regeneration after crush injury in rat sciatic nerve using immunohistochemistry and enzyme linked immunosorbent assay (ELISA). The number of TNF-immunopositive cells reached its peak and increased significantly in all the segments distal to the crush site 3 days after injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…These results do not rule out the possibility that more significant levels of TNF could have been detected at later time points after injury. In this regard, others have reported, using a similar lesion model, that TNF expression in the rodent sciatic nerve distal stump peaks at 3 d after injury (La Fleur et al, 1996;George et al, 2004;Sawada et al, 2007). The hybridization signal for the genes encoding IFN␤ and iNOS mRNA was comparable to background levels (data not shown).…”
Section: Resultsmentioning
confidence: 73%
“…These results do not rule out the possibility that more significant levels of TNF could have been detected at later time points after injury. In this regard, others have reported, using a similar lesion model, that TNF expression in the rodent sciatic nerve distal stump peaks at 3 d after injury (La Fleur et al, 1996;George et al, 2004;Sawada et al, 2007). The hybridization signal for the genes encoding IFN␤ and iNOS mRNA was comparable to background levels (data not shown).…”
Section: Resultsmentioning
confidence: 73%
“…This early peak is followed by a second, later phase of increased cytokine expression [9, 10]. A second phase of IL-1 β , TNF α and IL-10 upregulation [12, 13] and period of axon growth [14] occur within 7 days after nerve crush injury. Our immunofluorescence staining results have shown that, in addition to invaded macrophages and other immune cells [1517], Schwann cells constitute another robust source of both pro- and anti-inflammatory cytokines distal to nerve crush injury for 7 d. In addition, double immunostaining revealed that GAP43+ growing axons are in close contact with Schwann cells strongly decorated by immunofluorescence for IL-1 β , TNF α , IL-4, and IL-10 (Figures 1(d)–1(i), 2(d)–2(i), 3(d)–3(i), and 4(d)–4(i)).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of IL-10 after nerve injury is an interesting subject, because it attenuates production of proinflammatory cytokines IL-1 β and TNF α . Significant increase of IL-10 and IL-10-immunopositive cells has been observed 7 d after nerve injury [13, 32]. Thus, IL-10 may promote axonal regeneration by inhibiting overproduction of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…SCs secrete many factors to recruit macrophages and modulate Wallerian degeneration, such as LIF, TNFα, IL-1α, and IL-1β [78,79]. LIF stimulates autocrine monocyte chemoattractant protein (MCP-1) expression in SCs [80] while TNFα and interleukin (IL-1β) have been linked to increased matrix metalloproteinase (MMP-9) [81,82], which are all involved in macrophage migration and recruitment.…”
Section: Response To Injurymentioning
confidence: 99%